2021
DOI: 10.1111/eva.13277
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 disruption reveals mass‐tourism pressure on nearshore sea turtle distributions and access to optimal breeding habitat

Abstract: Quantifying the extent to which animals detect and respond to human presence allows us to identify pressure (disturbance) and inform conservation management objectively; however, obtaining baselines against which to compare human impact is hindered in areas where human activities are already well established. For example, Zakynthos Island (Greece, Mediterranean) receives around 850,000 visitors each summer, while supporting an important loggerhead sea turtle rookery (~300 individuals/season). The coronavirus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…However, most of the plasticity appears to be maladaptive: turbid conditions lead males to spend more time by the nest, contrary to female preferred behaviour such as increased search activity and time spent by the female. Comparable changes in behaviours during the reproductive period were also observed in sea turtles ( Caretta caretta ) nesting in Zakynthos (Greece), whereby the presence of tourists forces the turtles to use suboptimal, slightly cooler waters, that slow‐down egg development (Schofield et al, 2021 ). The impact is a likely longer nesting period, which may result in lower hatching success, ultimately selecting for faster development with unknown consequences.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, most of the plasticity appears to be maladaptive: turbid conditions lead males to spend more time by the nest, contrary to female preferred behaviour such as increased search activity and time spent by the female. Comparable changes in behaviours during the reproductive period were also observed in sea turtles ( Caretta caretta ) nesting in Zakynthos (Greece), whereby the presence of tourists forces the turtles to use suboptimal, slightly cooler waters, that slow‐down egg development (Schofield et al, 2021 ). The impact is a likely longer nesting period, which may result in lower hatching success, ultimately selecting for faster development with unknown consequences.…”
Section: Introductionmentioning
confidence: 95%
“…The impact is a likely longer nesting period, which may result in lower hatching success, ultimately selecting for faster development with unknown consequences. The forced displacement of turtles was only visible because of the ban on travel related to the SARS‐CoV2 pandemic, which reduced the effects of tourist presence on turtle behaviours (Schofield et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…All UAS footage was reviewed manually by at least two independent observers. We recorded the longitude and latitude of each turtle detected on footage (accurate to within 55 cm; Dujon et al, 2021;Schofield et al, 2021), along with sex, behaviour, position in water column (i.e., seabed versus midwater, with midwater turtles having a shadow on the seabed), distance from shore and seabed depth. Previous field validation at the study site confirmed that the detection of turtles was reliably consistent at the surveyed depths and across surveys (Schofield et al, 2017).…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…Social media records were collected for 2019, 2020 and 2021 following the methods described in Papafitsoros et al (2021). The first year represented a typical tourism year (2019) and the next two years (2020 and 2021) were heavily and mildly impacted by COVID-19, respectively, when tourism levels were limited by global travel restrictions (Schofield et al, 2021). Instagram was selected over other social media types because of its popularity and convenient search framework via "hashtags" and "places".…”
Section: Collection Of Social Media Recordsmentioning
confidence: 99%
“…However, this demand (and consequent pressure) is not consistent within or across years (Moorhouse et al ., 2015), particularly in areas supporting seasonal migrants, such as breeding humpback whales and sea turtles. The recent COVID-19 pandemic exemplifies this issue via the unprecedented absence of ecotourism in hotspots globally, which provided new insights on animal behaviour and movement patterns in the absence of human disturbance (Rutz et al ., 2020; Bates et al ., 2021; March et al ., 2021; Schofield et al ., 2021). Even within the same population, animals are not randomly distributed in time or space, with certain individuals (in hotspots or residents) being disproportionately targeted (Semeniuk et al ., 2009; Christiansen and Lusseau, 2014).…”
Section: Introductionmentioning
confidence: 99%